US adolescents' response to nicotine warning labels in influencer e-cigarette marketing social media posts: a survey-based randomised between-subject experiment - Vassey, Julia; Vogel, Erin A; Unger, Jennifer B (Tobacco control, 2025)
E-cigarette promotional posts with misleading nicotine warning labels on social media may lower adolescents' risk perceptions of e-cigarettes. A between-subject experiment assessed effects of influencers' e-cigarette promotional posts with different nicotine warning labels on adolescents' e-cigarette harm perceptions, susceptibility to e-cigarette use and perceptions of influencer credibility. In 2022, adolescents (N=1864, M =17 (SD=0.6)) were randomised to view six images and videos featuring influencers promoting e-cigarettes in one of five experimental conditions: two conditions with a 'tobacco-free nicotine' warning label (placed on an e-cigarette in the post or at the top of the post), two conditions with the US Food and Drug Administration (FDA) nicotine warning label (on an e-cigarette in the post or at the top of the post (control)) and one no-label condition. Participants rated influencers' credibility (eg, honesty). Harm perceptions of, and susceptibility to use, e-cigarettes were then assessed. Participants who viewed posts with the FDA warning label at the top of the post perceived influencers as more honest, trustworthy and informed than in all the other conditions. E-cigarette never-users who viewed posts with a 'tobacco-free nicotine' warning label pictured on an e-cigarette (compared with the FDA label at the top of a post) were more likely to report susceptibility to e-cigarette use (adjusted OR 1.79, 95% CI 1.17 to 2.73). Alterations of the required nicotine warning labels can make them less effective in deterring e-cigarette use behaviour. Tobacco control authorities could increase enforcement of the FDA-required nicotine warning labels and harness influencers for antitobacco messaging.